2007
DOI: 10.1021/cm0705183
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Nanoscale Phosphor (Y0.95Tb0.05)2O2CO3 by Alkalide Reduction and Its Phase Transformation to (Y0.95Tb0.05)2O3

Abstract: Tb 0.05 ) 2 O 2 CO 3 nanoparticles have been synthesized by subambient homogeneous reduction using alkalide solutions and subsequent oxidation. As synthesized, the material consists of free flowing agglomerates of ill-defined, amorphous, or subnanocrystalline nanoparticles. Thermal analysis shows that 2.83 CO 2 molecules are adsorbed per Y 2 O 3 formula unit in the washed product. The samples annealed at 200 °C or greater are crystalline, consisting of agglomerated nanocrystals. The nanocrystals grow from an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…11 The 248 nm peak in the excitation spectra of directly synthesized (Y 0.95 Tb 0.05 ) 2 O 3 annealed at 500 C is not present when the material is annealed at higher temperature but is similar to that observed at 243 nm in the excitation spectra of (Y 0.95 Tb 0.05 ) 2 O 3 made by the indirect method and that of (Y 0.95 Tb 0.05 ) 2 O 2 CO 3 at 247 nm. 13 A very similar feature was reported for nanocrystalline Y 2 O 3 :Tb made by an unspecified microemulsion technique and is absent in the spectra of bulk samples; it has been suggested that the feature arises from quantum confinement occurring in nanocrystals less than 5 nm in diameter. 10 It should be noted that the model of quantum confinement suggested is markedly different to that widely invoked to explain the behavior of semiconductor nanomaterials and the reader is cautioned to read the referenced literature 10 to fully understand the analysis in this report.…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…11 The 248 nm peak in the excitation spectra of directly synthesized (Y 0.95 Tb 0.05 ) 2 O 3 annealed at 500 C is not present when the material is annealed at higher temperature but is similar to that observed at 243 nm in the excitation spectra of (Y 0.95 Tb 0.05 ) 2 O 3 made by the indirect method and that of (Y 0.95 Tb 0.05 ) 2 O 2 CO 3 at 247 nm. 13 A very similar feature was reported for nanocrystalline Y 2 O 3 :Tb made by an unspecified microemulsion technique and is absent in the spectra of bulk samples; it has been suggested that the feature arises from quantum confinement occurring in nanocrystals less than 5 nm in diameter. 10 It should be noted that the model of quantum confinement suggested is markedly different to that widely invoked to explain the behavior of semiconductor nanomaterials and the reader is cautioned to read the referenced literature 10 to fully understand the analysis in this report.…”
Section: Resultssupporting
confidence: 56%
“…Note that the annealing of the previously unheated material evolves a significant quantity of CO 2 , which, as we previously reported, results in the synthesis of the carbonate (Y 0.95 Tb 0.05 ) 2 O 2 CO 3 if the headspace in the sealed ampoule is insufficient, causing a buildup of many atmospheres of pressure. 13 Avoiding the production of the carbonate and instead producing the oxide requires one to limit the pressure that is developed in the ampule as CO 2 is desorbed from the starting material during heating. By decreasing the sample mass to ampoule volume ratio from 0.033 g ml À1 in the previous study, to 0.0057 g ml À1 in the current study, and consequently the pressure from the evolution of CO 2 during heating from $4.2 to $0.72 atm at 400 C, the carbonate phase is avoided and the oxide results instead.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations